A Review on Performance Improvement of Vortex Tube (International Journal of Advanced Research in Science, Management and Technology, 2022)
Now-a-days, the first and foremost important quality of any research or development is its eco-friendly nature. As we know environment safety has become an important aspect of the industries and people in common. Vortex tube is also known as non-conventional cooling device that will produce cold air and hot air when we passed compressed air from compressor without causing any harm to the nature. In vortex tube, when a compressed air from compressor is tangentially passed into vortex chamber vortex tube splits the compressed air into two parts: a free vortex as the peripheral warm stream at the conical valve end and a forced vortex as the inner cold stream through the orifice. It can be used for any type of spot cooling application. [1]
Keywords: Safety, Vortex tube, Compressed air, Stream, Orifice.